Empirical Analysis of Efficiency and Profitability of US banking industry from 2011 to 2017 - Jiang, Jiru (2018)
This dissertation aims to explore the efficiency and profitability of US 50 largest banks over the course of 2011 to 2017, which is after-crisis period. The whole research will be split into two parts. One is to estimate the cost efficiency scores for sample banks, by utilizing Stochastic Frontier Analysis (SFA). The other is to estimate the profitability model measured by ROAE and incorporated with efficiency scores obtained previously in the efficiency model. System Generalized Method of Moments (SGMM) will be employed to estimate the bank profitability model and prior to it, an endogeneity test will be performed as well. Detailed interpretation and results analysis will be carried out later and reasons to our research outcome could be briefly attributed to the after-crisis lagging effect and recovery from the Global Financial Crisis, together with regulation regime and new capital requirements implemented by Basel III and banks’ adaption to these new changes.